Philadelphia Union - Carothers, Thomas (2021)
Introduces soccer fans to the history of one of the top MLS clubs, Philadelphia Union. The title features informative sidebars, exciting photos, a timeline, team facts, a glossary, and an index. Aligned to Common Core Standards and correlated to state standards. --Adapted from Amazon.
Includes bibliographical references (page 47) and index.
Ages 8-12
Keywords: Philadelphia Union (Soccer team) -- History -- Juvenile literature; Soccer teams -- Pennsylvania -- Philadelphia -- History -- Juvenile literature; Soccer teams; Pennsylvania -- Philadelphia; History; Juvenile works